Education Sustainable Development-Integrated Organic Waste Management to Improve Students Sustainability Literacy - Havita, Vivit Nurhikmah; Hamidah, Ida; Sriyati, Siti (Jurnal Pendidikan MIPA, 2021)
Abstract: This article aims to explore a startegi in the form of the implementation of organic waste management to create sustainable skills and mindsets. The method used in this study is the weak method of experimentation. Instruments used in research in the form of instruments about 15 questions are tested before and after learning. The sample used in this study as many as 32 students in one of the junior high schools in Pandeglang. The results showed an increase between the pretest and postest student results with a significance level of 0.00 which showed that there was an influence between sustainable development education integrated organic waste management and improved sustainability literacy. While the acquisition of N-Gain score of 46.87% with low category, 46.87% medium category and 6.25% in the high category. N-Gain scores show less than optimal results, because some students get low N-Gain grades. Thus, this research can be concluded to be able to increase the sustainability literacy of students with low categories. Therefore, it needs to be re-studied for further research. The results of this study are also useful for anyone who wants to learn about sustainable lifestyles, especially in organic waste management.Keywords: science learning, sustainable development education, sustainability literacy. DOI: http://dx.doi.org/10.23960/jpmipa/v22i2.pp262-269